Injury Analysis in Professional Soccer by Means of Media Reports – Only Severe Injury Types Show High Validity - Krutsch V; Grechenig S; Loose O; Achenbach L; Zellner J; Striegel H; Alt V; Weber J; Braun M; Gerling S; Krutsch W (Dove Medical Press, 2020)
Volker Krutsch,1 Stephan Grechenig,2 Oliver Loose,3 Leonard Achenbach,4 Johannes Zellner,2 Heiko Striegel,5 Volker Alt,2 Johannes Weber,2 Markus Braun,6 Stephan Gerling,7 Werner Krutsch2 1Department of Otorhinolaryngology, Head and Neck Surgery, Paracelsus Medical University, General Hospital Nuremberg, Nuremberg, Germany; 2Department of Trauma Surgery, University Medical Center Regensburg, Regensburg, Germany; 3Clinic of Pediatric Surgery, Olga Hospital, Clinic Stuttgart, Stuttgart, Germany; 4Department of Trauma Surgery, University Hospital Würzburg, Würzburg, Germany; 5Department of Sports Medicine, University Hospital Tuebingen, Tuebingen, Germany; 6Department of Sports Medicine, Clinic Westfalen, Dortmund, Germany; 7Department of Paediatric and Young Adult Medicine, Clinic St. Hedwig, Barmherzige Brüder Regensburg, Regensburg, GermanyCorrespondence: Werner KrutschDepartment of Trauma Surgery, University Medical Center Regensburg, Franz-Josef-Strauß-Allee 11, Regensburg 93053, GermanyTel +49 941 9446805Email werner.krutsch@ukr.dePurpose: Injury data of professional soccer players obtained from media reports are frequently used in scientific research, but the accuracy of such data is still unclear.Patients and Methods: Injuries of professional soccer players of the German first and second league were documented by continuously screening media reports over one season (2015– 2016). After the season, the validity of media-reported injuries was anonymously analyzed by the team physicians of 8 different soccer clubs.Results: A total of 255 injuries of 240 players of 8 professional soccer teams had been published online, of which 146 were confirmed by the team doctors as correct, yielding a rate of 57.3% of confirmed media-reported injuries. In addition, 92 injuries without media registration were detected and added to the online statistics, resulting in 347 injuries and an overall weak validity of media-based data of 42.1%. Statistical analysis showed that the validity of media-reported injury data depended on both the individual soccer club and the body site affected by injury: publications on knee injuries (78.2%) had a higher validity than those on foot injuries (46.2%), and publications on severe injuries had a higher validity (joint dislocation: 100%; ligament rupture: 82.9%; fracture: 73.3%) than those on minor injuries. Publications on specific severe soccer injuries, such as anterior cruciate ligament (ACL) injuries, had a validity of 100%.Conclusion: Media-based injury data were only valid for a few severe injury types such as ACL injuries. In daily soccer routine and scientific research, media-based data should thus only be used in combination with specific criteria or verification processes.Keywords: professional football, injury, evidence, media-based, severe injury, ACL